2021
DOI: 10.1186/s12888-021-03594-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between impulsivity and orthorexia nervosa / healthy orthorexia: any mediating effect of depression, anxiety, and stress?

Abstract: Background There is a lack of studies investigating the possible mediating role of psychological factors, such as depression, anxiety and stress on orthorexic eating behaviors. Given that personality attributes might affect the manifestation of psychological disorders, it was hypothesized that depression, anxiety and stress mediate the relationship between impulsivity-related traits and orthorexic eating, noting that previous research had evaluated the role of depression as a mediator between i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 69 publications
2
21
0
1
Order By: Relevance
“…Greater scores reflect more impulsivity in each of the four subscales: perseverance (αCronbach = 0.65) premeditation (α = 0.79), urgency (α = 0.67), and sensation seeking (α = 0.68). The Arabic validated version used in the present study confirmed the original factor structure of the scale [42].…”
Section: Rosenberg Self-esteem Scale Validated In Arabicsupporting
confidence: 69%
“…Greater scores reflect more impulsivity in each of the four subscales: perseverance (αCronbach = 0.65) premeditation (α = 0.79), urgency (α = 0.67), and sensation seeking (α = 0.68). The Arabic validated version used in the present study confirmed the original factor structure of the scale [42].…”
Section: Rosenberg Self-esteem Scale Validated In Arabicsupporting
confidence: 69%
“…This possibly validates our finding that having prostate cancer was significantly correlated with lower scores on the DOS. A possible explanation for differences in these correlations between patients with breast cancer and patients with prostate cancer, is the gender difference between these cancer types, such that gender (i.e., being female) is associated with a higher prevalence of orthorexia nervosa, as has been previously established in several articles (Awad et al, 2021;Hallit, Barrada et al, 2021). This hypothesis is further fortified by a finding that the prevalence of women who place importance on the nutritional quality of foods is twice that of men (Olejniczak et al, 2017).…”
Section: Cancer Type and Gender In Relation To Orthorexiamentioning
confidence: 84%
“…In line with previous studies, we found that healthy orthorexia symptoms are associated negatively with depression and anxiety levels. 10,42,43 Healthy orthorexia assesses the interests of a healthy diet and is a separate construct from psychopathology. In addition, orthorexia nervosa symptoms correlated positively with depression and anxiety levels.…”
Section: Discussionmentioning
confidence: 99%